When "we" leave "them": Distinguishing schisms from individual exit. (11th June 2019) - Wagoner, Joseph A.; Barreto, Nicolas; Rinella, Mark J.
Abstract: Schisms occur when a faction breaks away from their parent group to create or to join an already existing group. However, previous researchers who have examined schisms have primarily focused on people's individual intentions to exit their group. This poses two questions: first, does a schism involve both breaking away from a parent group and forming a new group? And second, are the psychological processes that predict individual exit intentions also predicting people's support of schisms, or are there distinct psychological processes involved in a schism? Study 1 ( N  = 284) confirmed that a schism consists of two subcomponents: subgroup exit and superordinate formation . Study 2 ( N  = 261) showed that the psychological processes related to individual exit intentions are distinct from those processes related to schisms. Results suggest that support for schisms is distinct from individual exit intentions and that there are unique psychological predictors of schisms.